Impacts of the COVID-19 pandemic on healthcare access among patients receiving medication for opioid use disorder - Jacka, Brendan P.; Janssen, Tim; Garner, Bryan R.; Yermash, Julia; Yap, Kimberly R.; Ball, Elizabeth L.; Hartzler, Bryan; Becker, Sara J. (Drug and alcohol dependence, 2021)
•Patients receiving medication for opioid use disorder are vulnerable to COVID-19 impacts.•Negative impacts include increased drug use and difficulty accessing healthcare.•Subgroup analysis identified three distinct subgroups of substance use at enrolment.•Polysubstance use subgroup had greatest difficulty accessing harm reduction services. The COVID-19 pandemic significantly altered treatment delivery for opioid treatment programs (OTPs) dispensing medications for opioid use disorder (MOUD). We aimed to identify patterns of substance use among MOUD patients and examine whether COVID-19-related impacts on access to healthcare varied across subgroups. This analysis was embedded within a type 3 hybrid trial that enrolled patients across eight OTPs at the start of the pandemic. Enrolled patients reported on past-30 day use of multiple substances during their baseline assessment. Participants re-contacted in May–July 2020 completed a survey about COVID-19-related impacts on various life domains. Using latent class analysis we identified patient subgroups, and then examined group differences on a set of negative and positive COVID-19 impacts related to healthcare access. Of the 188 trial participants, 135 (72 %) completed the survey. Latent class analysis identified three MOUD patient subgroups: minimal use (class probability: 0.25); opioid use (class probability: 0.34); and polysubstance use (class probability: 0.41). Compared to the minimal use group, the polysubstance use group reported increased substance use and difficulty accessing sterile needles, naloxone, and preferred substance. The opioid use group reported increased substance use and difficulty accessing their preferred substance. There were no significant group differences related to accessing routine or specialized healthcare or medication; or paying attention to their health. During COVID-19, many MOUD patients reported challenges accessing care, particularly harm reduction services for patients with polysubstance use. Additional efforts, like providing wraparound support, may be necessary to serve the needs of MOUD patients.